Improvement in Semen Conservation of the Indigenous Czech Endangered Old Kladruber Horse: Special Focus on the Type of Extender and Packaging System - Šichtař, Jiří; Šimoník, Ondřej; Bubeníčková, Filipa; Svobodová, Jitka; Nehasilová, Anežka (Journal of equine veterinary science, 2019)
The aim of our study was to investigate the effect of two freezing extenders and two packaging systems on motility, plasma membrane (PM) integrity, and the apoptotic status of frozen-thawed (F-T) spermatozoa of the endangered Old Kladruber stallions. The collected semen (n = 6 stallions, three collections each) was diluted either with Gent or Lactose-EDTA (Lact) extender. Two aliquots of semen from each collection diluted in this way were prepared and then loaded into 5-mL aluminum tubes or 0.5-mL plastic straws. After thawing and then at 15 minutes intervals within 1 hour, the samples were analyzed for motility (CASA), PM integrity (CFDA/PI), and apoptotic changes of the spermatozoa (Yo-Pro-1/PI). Using Gent, the samples exhibited higher motility, kinematic parameters, higher representation of spermatozoa in medium, and fast subpopulation, as well as more spermatozoa with intact PMs and fewer spermatozoa with apoptotic changes compared with Lact extender (P < .05). Progressive motility and PM integrity was superior when using Gent and 5-mL aluminum tubes as compared with the rest of the combinations (P < .05). Kinematic parameters, percentage of spermatozoa in fast subpopulation and apoptotic status was superior in Gent and 0.5-mL straws as compared with the rest of the combinations (P < .05). Moreover, we revealed that F-T semen reacts diametrically differently when two different extenders and packaging systems are used. The study concludes that the combination of Gent and 0.5-mL straws represent adequate freezing system to maintain the appropriate quality of spermatozoa of this endangered breed.
Keywords: kryoprotektivní látky; Male; Sperm Motility; Cryopreservation; Česká republika; mužské pohlaví; Czech Republic; sperma; Semen; Animals; Cryoprotective Agents; lidé; Sperm; Straw; Humans; zvířata; motilita spermií; koně; Aluminum tube; kryoprezervace; Stallion; Horses